The Impact of Islamic Law on Human Rights Abuses in Conflict Zones - Abduljabbar, Firas Meshhal; Ahmed, Sundus Serhan; Abdulameer, Nibras Arif; Jawad, Haider Mahmood; Umirbekovna, Kubeeva Zhanar (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
The article explores the interplay between international law and Islamic jurisprudence in mitigating human rights violations in conflict zones, emphasizing compliance and enforcement challenges. Given the persistent human rights abuses in crisis areas, ranging from torture to extrajudicial killings, this study highlights the role of international conventions and treaties in curtailing such breaches. Employing a mixed-methods approach, the study quantitatively evaluates human rights violations against international treaties and Sharia principles over the past 30 years, alongside qualitative case studies that consider geopolitical contexts and the influence of international organizations. Preliminary findings indicate that while some infractions have declined in nations that actively engage with international bodies and adhere to Sharia principles, others persist, particularly in regions lacking effective international oversight. The article concludes that both international and Islamic legal systems must reassess their frameworks to enhance human rights protections, as the enforcement of treaties and Sharia laws remains challenging in wartime contexts. Strengthening the integration of Islamic jurisprudence within international law may offer additional avenues for safeguarding human rights in these vulnerable areas.